AYATISASI MASJID DI SUMATERA SEBAGAI FENOMENA LIVING AL-QUR’AN Telaah Atas Tren, Motif, Dan Dampaknya Bagi Kemakmuran Umat - Sawaluddin Siregar; Hasiah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The phenomenon of mosque ayatisation in Sumatra reflects a new trend in Islamic religious practice, representing efforts to bring Qur’anic values to life within the social sphere. This study aims to analyze the trends, motives, and impacts of ayatisation on mosque prosperity through the living Qur’an approach. Employing a qualitative method with a phenomenological framework and field research, the study was conducted in several mosques across Sumatra that have implemented ayatisation in architectural design, spatial aesthetics, and religious activities. Data were collected through observation, in-depth interviews, and visual documentation, and were thematically analyzed to reveal the religious and social implications of this practice. The findings indicate that mosque ayatisation has emerged as a form of contemporary religiosity rooted in the collective desire to visualize and internalize Qur’anic values within worship spaces. The primary motives include spiritual devotion, Islamic educational orientation, and the strengthening of communal religious identity. The positive impacts of ayatisation are evident in the increased participation of congregants, the enhancement of mosques’ social roles, and the revitalization of prosperity grounded in the values of rahmatan lil ‘alamin. This study concludes that ayatisation serves as a tangible manifestation of the living Qur’an, fostering stronger connections between the sacred text, worship spaces, and the social transformation of Muslim communities in Sumatra.